Deportiert nach Mauthausen: Europa in Mauthausen. Geschichte der Überlebenden eines nationalsozialistischen Konzentrationslagers, Band 2 - Alexander Prenninger; Regina Fritz; Gerhard Botz; Melanie Dejnega (2021)
"Europe in Mauthausen" presents a comprehensive history of the survivors of a Nazi concentration camp and is based on a unique collection of 859 oral and video history interviews with with former concentration camp prisoners in Europe, Israel, North and South America. The second volume examines how prisoners from numerous European countries were brought to the Mauthausen concentration camp complex. The deportations, the transfers of prisoners within the Nazi camp system and the death marches led to constant changes in the camp society; despite the omnipresence of violent death; thus, the fates of the inmates differed considerably.